Study on a new electromagnetic flowmeter based on three-value trapezoidal wave excitation. (April 2021) - Ge, Liang; Chen, Junxian; Tian, Guiyun; Ahmed, Junaid; Huang, Qi; Hu, Ze
Abstract: Excitation technology plays an important part in the field of electromagnetic flowmeter (EMF). The form of the magnetic field directly determines the characteristics of the flow signal. No breakthrough has been made on the excitation technology since the invention of sinusoidal wave excitation, rectangular wave excitation, and double-frequency excitation. In this paper, firstly a new three-value trapezoidal wave excitation with transient responses is proposed. Then the signal model is established, and the verification experiments are carried out. Finally, flow calibration experiments and comparative experiments on the trapezoidal wave excitation are conducted on the experimental platform. The experiment results show that the electromotive force output by the EMF based on three-value trapezoidal wave excitation is linearly related to the flow velocity. When the flow velocity is 0.257 m/s, the relative error is only 1.635%. When the flow velocity reaches 2.133 m/s, the relative error is reduced to 0.432%. The three-value trapezoidal wave excitation with the transient analysis satisfies the requirements of the EMF with high accuracy. The research also shows that the excitation frequency has a great influence on the measurement accuracy of the EMF based on three-value trapezoidal wave excitation. Highlights: New excitation technique is proposed and investigated in the electromagnetic flowmeter (EMF). The anti-interference ability and measurement accuracy of the EMF are tested and evaluated. The inter-electrode signal analysis based on the excitation is established. Three-value trapezoidal wave excitation EMF meets the needs of high-precision measurement.